Efficacy of immune checkpoint inhibitors for in-transit melanoma. Issue 1 (5th May 2020) - Nan Tie, Emilia; Lai-Kwon, Julia; Rtshiladze, Michael Alexander; Na, Lumine; Bozzi, James; Read, Tavis; Atkinson, Victoria; Au-Yeung, George; Long, Georgina V; McArthur, Grant A; Sandhu, Shahneen; Saw, Robyn; et al.
Abstract : Background: The efficacy of immune checkpoint inhibitors (ICI) in metastatic melanoma is well established. However, there are limited data regarding their efficacy in in-transit melanoma (ITM). This study assessed the efficacy of ICI in patients with ITM. Methods: A retrospective review of patients with ITM commenced on an ICI between March 2013 and February 2018 at three tertiary centers in Australia. Patients were excluded if they had previous or synchronous distant metastases. Overall response rate (ORR), progression-free survival (PFS) and overall survival (OS) were based on a composite of radiological and clinical assessments. Results: Fifty-four patients were included: 27 (50%) female; median age 75 (range 26–94); 12 (22%) stage IIIB, 40 (74%) stage IIIC and 2 (4%) stage IIID; 10 (19%) BRAF mutant. Forty (74%) received single-agent anti-PD-1 (pembrolizumab or nivolumab), 8 (15%) single agent anti-CTLA-4 (ipilimumab), 5 (9%) combination anti-PD-1/anti-CTLA-4 (ipilimumab and nivolumab or pembrolizumab) and 1 (2%) combination anti-PD-L1 (atezolizumab) and MEK inhibitor (cobimetinib). The median follow-up was 15 months (2–46). ORR to ICI was 54%: 14 (26%) complete responses; 15 (28%) partial responses; 9 (17%) stable disease; 16 (30%) progressive disease. Thirteen (46%) responders had only one ITM lesion. ORR was 58% for single-agent anti-PD-1, 38% for single-agent anti-CTLA4 and 40% for anti-PD-1/anti-CTLA-4. The median PFS was 11.7 months (6.6-not reached). 1-year and 2-year PFS were 48% and 39%, respectively, . Fourteen progressed locoregionally and 11 progressed distantly. The median OS was not reached. 1-year and 2-year OS were 85% and 63%, respectively. No clinicopathological features were associated with ORR. Conclusions and relevance: ICI produce objective responses in ITM and should be considered in patients with unresectable ITM or disease recurrence.